A versatile ex vivo technique for assaying tumor angiogenesis and microglia in the brain - Ghoochani, Ali; Yakubov, Eduard; Sehm, Tina; Fan, Zheng; Hock, Stefan; Buchfelder, Michael; Eyüpoglu, Ilker Yasin; Savaskan, Nicolai E. (Oncotarget, 2016)
Primary brain tumors are hallmarked for their destructive activity on the microenvironment and vasculature. However, solely few experimental techniques exist to access the tumor microenvironment under anatomical intact conditions with remaining cellular and extracellular composition. Here, we detail an ex vivo vascular glioma impact method (VOGIM) to investigate the influence of gliomas and chemotherapeutics on the tumor microenvironment and angiogenesis under conditions that closely resemble the in vivo situation. We generated organotypic brain slice cultures from rats and transgenic mice and implanted glioma cells expressing fluorescent reporter proteins. In the VOGIM, tumor-induced vessels presented the whole range of vascular pathologies and tumor zones as found in human primary brain tumor specimens. In contrast, non-transformed cells such as primary astrocytes do not alter the vessel architecture. Vascular characteristics with vessel branching, junctions and vessel meshes are quantitatively assessable as well as the peritumoral zone. In particular, the VOGIM resembles the brain tumor microenvironment with alterations of neurons, microglia and cell survival. Hence, this method allows live cell monitoring of virtually any fluorescence-reporter expressing cell. We further analyzed the vasculature and microglia under the influence of tumor cells and chemotherapeutics such as Temozolamide (Temodal/Temcad®). Noteworthy, temozolomide normalized vasculare junctions and branches as well as microglial distribution in tumor-implanted brains. Moreover, VOGIM can be facilitated for implementing the 3Rs in experimentations. In summary, the VOGIM represents a versatile and robust technique which allows the assessment of the brain tumor microenvironment with parameters such as angiogenesis, neuronal cell death and microglial activity at the morphological and quantitative level.
EVALuna2:22857

Chemotherapeutic xCT inhibitors sorafenib and erastin unraveled with the synaptic optogenetic function analysis tool - Dahlmanns, Marc; Yakubov, Eduard; Chen, Daishi; Sehm, Tina; Rauh, Manfred; Savaskan, Nicolai; Wrosch, Jana Katharina (Cell Death Discovery, 2017)
In the search for new potential chemotherapeutics, the compounds' toxicity to healthy cells is an important factor. The brain with its functional units, the neurons, is especially endangered during the radio- and chemotherapeutic treatment of brain tumors. The effect of the potential compounds not only on neuronal survival but also neuronal function needs to be taken into account. Therefore, in this study we aimed to comprehend the biological effects of chemotherapeutic xCT inhibition on healthy neuronal cells with our synaptic optogenetic function analysis tool (SOFA). We combined common approaches, such as investigation of morphological markers, neuronal function and cell metabolism. The glutamate-cystine exchanger xCT (SLC7A11, system Xc-) is the main glutamate exporter in malignant brain tumors and as such a relevant drug target for treating deadly glioblastomas (WHO grades III and IV). Recently, two small molecules termed sorafenib (Nexavar) and erastin have been found to efficiently block xCT function. We investigated neuronal morphology, metabolic secretome profiles, synaptic function and cell metabolism of primary hippocampal cultures (containing neurons and glial cells) treated with sorafenib and erastin in clinically relevant concentrations. We found that sorafenib severely damaged neurons already after 24 h of treatment. Noteworthy, also at a lower concentration, where no morphological damage or metabolic disturbance was monitored, sorafenib still interfered with synaptic and metabolic homeostasis. In contrast, erastin-treated neurons displayed mostly inconspicuous morphology and metabolic rates. Key parameters of proper neuronal function, such as synaptic vesicle pool sizes, were however disrupted following erastin application. In conclusion, our data revealed that while sorafenib and erastin effectively inhibited xCT function they also interfered with essential neuronal (synaptic) function. These findings highlight the particular importance of investigating the effects of potential neurooncological and general cancer chemotherapeutics also on healthy neuronal cells and their function as revealed by the SOFA tool.
EVALuna2:33743

Glial Glutamate Transporter-Mediated Plasticity: System xc -/xCT/SLC7A11 and EAAT1/2 in Brain Diseases - Dahlmanns, Marc; Dahlmanns, Jana; Savaskan, Nicolai; Steiner, Hans Herbert; Yakubov, Eduard (Frontiers in Bioscience - Landmark, 2023)
Glial cells play an essential role in the complex function of the nervous system. In particular, astrocytes provide nutritive support for neuronal cells and are involved in regulating synaptic transmission. Oligodendrocytes ensheath axons and support information transfer over long distances. Microglial cells constitute part of the innate immune system in the brain. Glial cells are equipped with the glutamatecystine- exchanger xCT (SLC7A11), the catalytic subunit of system xc -, and the excitatory amino acid transporter 1 (EAAT1, GLAST) and EAAT2 (GLT-1). Thereby, glial cells maintain balanced extracellular glutamate levels that enable synaptic transmission and prevent excitotoxic states. Expression levels of these transporters, however, are not fixed. Instead, expression of glial glutamate transporters are highly regulated in reaction to the external situations. Interestingly, such regulation and homeostasis is lost in diseases such as glioma, (tumor-associated) epilepsy, Alzheimer's disease, Parkinson's disease, amyotrophic lateral sclerosis or multiple sclerosis. Upregulation of system xc - (xCT or SLC7A11) increases glutamate export from the cell, while a downregulation of EAATs decreases intracellular glutamate import. Occurring simultaneously, these reactions entail excitotoxicity and thus harm neuronal function. The release of glutamate via the antiporter system xc - is accompanied by the import of cystine-an amino acid essential in the antioxidant glutathione. This homeostasis between excitotoxicity and intracellular antioxidant response is plastic and off-balance in central nervous system (CNS) diseases. System xc - is highly expressed on glioma cells and sensitizes them to ferroptotic cell death. Hence, system xc - is a potential target for chemotherapeutic add-on therapy. Recent research reveals a pivotal role of system xc - and EAAT1/2 in tumor-associated and other types of epilepsy. Numerous studies show that in Alzheimer's disease, amyotrophic lateral sclerosis and Parkinson's disease, these glutamate transporters are dysregulated-and disease mechanisms could be interposed by targeting system xc - and EAAT1/2. Interestingly, in neuroinflammatory diseases such as multiple sclerosis, there is growing evidence for glutamate transporter involvement. Here, we propose that the current knowledge strongly suggest a benefit from rebalancing glial transporters during treatment.
CRIS-Team Scopus Importer:2023-04-14
Keywords: Alzheimer's disease; amyotrophic lateral sclerosis; GLAST; glioma; GLT-1; neuroinflammation; Parkinson's disease; SLC7A11

Glioblastoma cells induce differential glutamatergic gene expressions in human tumor-associated microglia/macrophages and monocyte-derived macrophages - Choi, Judy; Stradmann-Bellinghausen, Beate; Yakubov, Eduard; Savaskan, Nicolai E.; Regnier-Vigouroux, Anne (Cancer Biology & Therapy, 2015)
Glioblastoma cells produce and release high amounts of glutamate into the extracellular milieu and subsequently can trigger seizure in patients. Tumor-associated microglia/macrophages (TAMs), consisting of both parenchymal microglia and monocytes-derived macrophages (MDMs) recruited from the blood, are known to populate up to 1/3 of the glioblastoma tumor environment and exhibit an alternative, tumor-promoting and supporting phenotype. However, it is unknown how TAMs respond to the excess extracellular glutamate in the glioblastoma microenvironment. We investigated the expressions of genes related to glutamate transport and metabolism in human TAMs freshly isolated from glioblastoma resections. Quantitative real-time PCR analysis showed (i) significant increases in the expressions of GRIA2 (GluA2 or AMPA receptor 2), SLC1A2 (EAAT2), SLC1A3 (EAAT1), (ii) a near-significant decrease in the expression of SLC7A11 (cystine-glutamate antiporter xCT) and (iii) a remarkable increase in GLUL expression (glutamine synthetase) in these cells compared to adult primary human microglia. TAMs co-cultured with glioblastoma cells also exhibited a similar glutamatergic profile as freshly isolated TAMs except for a slight increase in SLC7A11 expression. We next analyzed these genes expressions in cultured human MDMs derived from peripheral blood monocytes for comparison. In contrast, MDMs co-cultured with glioblastoma cells compared to MDMs co-cultured with normal astrocytes exhibited decreased expressions in the tested genes except for GLUL. This is the first study to demonstrate transcriptional changes in glutamatergic signaling of TAMs in a glioblastoma microenvironment, and the findings here suggest that TAMs and MDMs might potentially elicit different cellular responses in the presence of excess extracellular glutamate.
EVALuna2:22851

MIF-CD74 signaling impedes microglial M1 polarization and facilitates brain tumorigenesis - Ghoochani, Ali; Schwarz, Martin; Yakubov, Eduard; Engelhorn, Tobias; Dörfler, Arnd; Buchfelder, Michael; Bucala, R.; Savaskan, N. E.; Eyupoglu, I. Y. (Oncogene, 2016)
Microglial cells in the brain tumor microenvironment are associated with enhanced glioma malignancy. They persist in an immunosuppressive M2 state at the peritumoral site and promote the growth of gliomas. Here, we investigated the underlying factors contributing to the abolished immune surveillance. We show that brain tumors escape pro-inflammatory M1 conversion of microglia via CD74 activation through the secretion of the cytokine macrophage migration inhibitory factor (MIF), which results in a M2 shift of microglial cells. Interruption of this glioma-microglial interaction through an antibody-neutralizing approach or small interfering RNA (siRNA)-mediated inhibition prolongs survival time in glioma-implanted mice by reinstating the microglial pro-inflammatory M1 function. We show that MIF-CD74 signaling inhibits interferon (IFN)-γ secretion in microglia through phosphorylation of microglial ERK1/2 (extracellular signal-regulated protein kinases 1 and 2). The inhibition of MIF signaling or its receptor CD74 promotes IFN-γ release and amplifies tumor death either through pharmacological inhibition or through siRNA-mediated knockdown. The reinstated IFN-γ secretion leads both to direct inhibition of glioma growth as well as inducing a M2 to M1 shift in glioma-associated microglia. Our data reveal that interference with the MIF signaling pathway represents a viable therapeutic option for the restoration of IFN-γ-driven immune surveillance.
EVALuna2:33151

PRG3 induces Ras-dependent oncogenic cooperation in gliomas - Fan, Zheng; Bittermann-Rummel, Philipp; Yakubov, Eduard; Chen, Daishi; Broggini, Thomas; Sehm, Tina; Hatipoglu Majernik, Gökce; Hock, Stefan; Schwarz, Marc; Engelhorn, Tobias; Dörfler, Arnd; Buchfelder, Michael; et al. (Oncotarget, 2016)
Malignant gliomas are one of the most devastating cancers in humans. One characteristic hallmark of malignant gliomas is their cellular heterogeneity with frequent genetic lesions and disturbed gene expression levels conferring selective growth advantage. Here, we report on the neuronal-associated growth promoting gene PRG3 executing oncogenic cooperation in gliomas. We have identified perturbed PRG3 levels in human malignant brain tumors displaying either elevated or down-regulated PRG3 levels compared to non-transformed specimens. Further, imbalanced PRG3 levels in gliomas foster Ras-driven oncogenic amplification with increased proliferation and cell migration although angiogenesis was unaffected. Hence, PRG3 interacts with RasGEF1 (RasGRF1/CDC25), undergoes Ras-induced challenges, whereas deletion of the C-terminal domain of PRG3 (PRG3ΔCT) inhibits Ras. Moreover PRG3 silencing makes gliomas resistant to Ras inhibition. In vivo disequilibrated PRG3 gliomas show aggravated proliferation, invasion, and deteriorate clinical outcome. Thus, our data show that the interference with PRG3 homeostasis amplifies oncogenic properties and foster the malignancy potential in gliomas.
EVALuna2:23011